Physical attributes of soil and its relation with space prodictivity of coffee arabic - Silva, Samuel de Assis; Lima, Julião Soares de Souza (Coffee Science - ISSN 1984-3909, 2014)
The aim of this study was to determine the distribution of soil physical properties and assess their spatial relationship to the productivity of arabica coffee, using it, multivariate geostatistics. The experiment was conducted in a cultivated area five years ago with Coffea arabica L. Catuaí in an humic dystrophic Red-Yellow. For mapping soil and raising crop productivity, we constructed a sampling grid, totaling 100 georeferenced points. The physical attributes studied were the fractions (coarse sand, fine sand, silt and clay) and soil bulk density. Data were analyzed using descriptive statistics and exploratory, and the relationship between physical attributes and yield were analyzed by Pearson correlation. hen the data were subjected to geostatistical analysis in order to verify the existence and, if so, to quantify the degree of spatial dependence of attributes and productivity and the relationship between them. The productivity of coffee correlated with soil physical properties except silt, since it was recorded positive correlation with the other textural and negative fractions with soil density. Both productivity and physical soil properties showed spatial distribution with high spatial continuity. The “cokriging” was efficient to map the spatial distribution of productivity, using as covariates the physical attributes of the soil.